Hulk (2021), volume 2 ebook Hulk planet. - Cates, Donny (Hulk (2021), 2023)
Collects Hulk (2021) #9-14. Journey to a Hulk Planet! Thoroughly shaken by his battle with Thor - and by Titan's impact on his friends - Bruce Banner finds what should be the ultimate paradise: an entire planet of Hulk-like creatures thriving under the heat of a gamma star. But even at the center of a civilization that worships him, Bruce can't shake thoughts of the past - and he should know by now that he can never find peace for long. For Titan, the darkest part of the Hulk, refuses to remain caged like an animal. And when Titan finally breaks free, he'll be looking for a vicious and violent fight! It's the mind-blowing finale to Donny Cates and Ryan Ottley's blockbuster saga of Starship Hulk!